Use of walking tractor powered rotary tiller in no-tillage system - Medeiros, Fabricio (2014)
Brazilian family farming has at its disposal planters whose furrowing mechanisms, whether disc or shank, require a large vertical force. In smaller planters, this is reflected in low efficiency when opening the furrow or in a high demand for mass (weight). Rotary furrowers require less vertical force for the same operation. This study aimed to evaluate the technical feasibility and performance of rotary furrowers mounted on the powertrain of a walking tractor working under direct seeding, and compare them with shank-type furrowers using bibliographic data. The parameters used in the comparison were the depth and width of the furrow, the area of disturbed soil and the cross-sectional area of the furrow with no soil after the operation. The experiment was carried out on wheat stubble that had lain fallow for six months. Twelve treatments were employed in a factorial design: three models of rotary furrowers, two values for revolutions per unit of linear displacement, and two forward speeds. The variable, cross-sectional area of the furrow with no soil, was statistically affected only by the factor, furrower. However there was significant interaction between the factors, furrower, revolutions per metre and speed, for the variables of depth, furrow width and area of disturbed soil. The values obtained for the variables of width, depth and disturbed area in the cross-section of the furrows, with the three types of rotary furrowers driven by the powertrain of a walking tractor, were similar to those generated by shank-type furrowers.